Spontaneous Superior Mesenteric Artery Branch Pseudoaneurysm: A Rare Case Report - Guirgis, Mina (EJVES Short Rep, 2017)
BACKGROUND: Visceral arterial pseudoaneurysms (VAPAs) are rare vascular entities with serious consequences. Traditionally, they are associated with trauma, infection, and inflammatory disease, or they can arise as a post-operative complication. REPORT: An 87 year old man presented with abdominal pain and was found to have a spontaneous VAPA on a computed tomography angiogram. Serial imaging 4 months previously had demonstrated no aneurysm. Between scans, warfarin was changed to apixaban for aortic valve replacement, but he had no other changes to any other medications. He required urgent endovascular coiling of the pseudoaneurysm, with satisfactory recovery and outcome. DISCUSSION: VAPAs are extremely rare, with splenic artery VAPAs the most commonly reported. Regardless, fewer than 250 cases of splenic artery pseudoaneurysm have been reported. Superior mesenteric artery (SMA) pseudoaneurysms are the rarest type of VAPAs. Early identification and urgent treatment are warranted because of the associated high mortality risk, with a 50% risk of rupture in any given VAPA. Treatment options range from open operation to endoscopic and endovascular procedures. Apixaban has been proposed to contribute to pseudoaneurysm formation by slow and continuous bleeding that results in the formation of the pseudoaneurysm. CONCLUSIONS: Spontaneous VAPAs are extremely rare and this is the first time a VAPA has been associated with the novel oral anticoagulant “apixaban”. Urgent management of any VAPAs is important because of the high risk of rupture and potential life threatening haemorrhage.